Evaluation of Efficacy of Neuro Muscular Electrical Stimulation and Electro Acupuncture in Improving the Pain and Disability in Patients with the Lumbar Degenerative Intervertebral Disk Disease - Salehi, Shahin; Faraji Qomi, Zeinab; Hesami, Omid; Poursaeid Esfahani, Mehrshad; Abedi Yekta, Amirhosein; Hassabi, Mohammad; Sohrabi, Mohammad Reza; Elahi, Morvarid (Novelty in Biomedicine, 2020)
Background: Chronic low back pain (CLBP) due to the degenerative intervertebral disk diseases is one of the most common musculoskeletal conditions in contemporary societies. A variety of pharmacological, non-pharmacological and surgical options is available for treatment of CLBP. The use of non-pharmacological methods have drastically increased in recent years, offering fewer complications and expenses. This study was conducted to compare the efficacy of the neuromuscular electrical stimulation (NMES) and electro acupuncture (EAP) with exercise therapy alone in patients with chronic low back pain. Materials and Methods: This was a randomized case-controlled clinical trial. Sixty patients with CLBP were randomly assigned to 3 groups (20 cases each) of the EAP with exercise therapy, NMES with exercise therapy, and exercise therapy only. Severity of pain and disability improvement were assessed using the visual analog scale (VAS) and Quebec back pain disability scale respectively. Results: A total of 66 individuals were enrolled, out of which 6 were excluded due to patients’ lack of cooperation. A significant decline in the amounts of Quebec and VAS was observed in the three groups (p<0.001). The pain and disability improvements did not display any significant difference in the NMES or EAP groups compared to the control group. However, the severity of disability and pain in the NMES group were significantly higher than the EAP group (p<0.05). Conclusion: These findings may indicate an almost identical efficacy of exercise therapy alone compared to the combination with electrical stimulation techniques in improving the pain and disability in patients suffering CLBP.